A solution processed metal–oxo cluster for rewritable resistive memory devices. Issue 4 (18th December 2018) - Zhou, Kui; Ding, Guanglong; Zhang, Chen; Lv, Ziyu; Luo, Shenghuang; Zhou, Ye; Zhou, Li; Chen, Xiaoli; Li, Huilin; Han, Su-Ting
Abstract : A memory device based on metal–oxo cluster-assembled materials demonstrates a redox-based resistive switching behaviour which is correlated with the migration of hydroxide ions with low activation energy. Abstract : Understanding the mobility and electrochemical process of ion species at the nanoscale is the key step to obtain high performance non-volatile data storage devices. Here, we present a systematic study on the resistive switching mechanism of an assembled metal–oxo cluster [Bi6 O4 (OH)4 ](NO3 )6 (BiON) to build reliable non-volatile memory devices. The bipolar resistive-switching with low operation voltage is observed and is attributed to the migration of ion species (mainly OH − ) with low activation energy (∼0.20 eV) along the polar electric field and simultaneous valence change of the bismuth of the [Bi6 O4 (OH)4 ] clusters in the BiON film. The X-ray photoelectron spectroscopy (XPS), conductive atomic force microscopy (CAFM) and Kelvin probe force microscopy (KPFM) characterization confirms that OH − with low activation energy is expected to facilitate the formation and rupture of anion vacancy filaments. Moreover, intermediate oxide layers formed at the Al/BiON interfaces could help to stabilize and assist the resistive switching. The control of the clusters and counter-ion species in the metal–oxo cluster-assembled materials represents a step toward next generation multi-level, high-speed and low energy consumption non-volatile memory devices for in-memory computing and artificial intelligence.